Crop diversification through vegetable inter-cropping system under Farmer FIRST Programme in Varanasi - Singh, S K; Roy, Shubhadeep; Singh, Neeraj; Bhardwaj, D R; Singh, Jagdish (Indian Farming, 2022)
In recent decades, agricultural diversification has increasingly been considered as a panacea for the severe problems that have afflicted agriculture. Crop diversification including different cereal and horticultural crops in the cropping sequence can provide farmers with a better income. Therefore, a key step is to diversify the cereal-based production system through the inclusion of vegetable crops in the cropping sequence. Inclusion of vegetables in the major cropping systems will not only improve the availability of vegetables and help in food selfsufficiency but will also provide means to earn foreign exchange by exporting fresh vegetables and vegetable seeds. Moreover, these vegetable crops are suitable for production on small pieces of land and their inclusion in traditional cropping systems can improve the nutritional potential of the system.